EVALUASI TEBAL PERKERASAN LAPIS TAMBAH DENGAN MENGGUNAKAN PROGRAM EVERSERIES DAN METODE BINA MARGA Studi kasus : Jalan Tol JAGORAWI ruas Jalan TMII - Cibubur - Grandy Hellyantoro; Mohammad Faldi Fauzi; Bagus Hario Setiadji; Wahyudi Kushardjoko (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Road maintenance and rehabilitation program is a program to improve functional condition of a road pavement. EVERSERIES 5.0 is a group of programs having an ability to do a complex analysis especially in determining pavement respond and modulus, and also designing pavement overlay, i.e. EVERSTRESS, EVERCALC and EVERPAVE, respectively.The objective of this research was to evaluate Bina Marga Pd T-05-2005-B Guideline in designing overlay thickness by comparing the guideline with EVERSERIES program. The location of the study was TMII – Cibubur segment of Jagorawi toll road. For the purpose of the research, two-way (direction A and B) deflection data along the segment together with 5-year traffic volume data were collected. In determining overlay thickness, EVERSERIES program firstly evaluated the existing deflection and pavement temperature data and used them in backcalculation process to produce elastic moduli. The moduli, together with traffic volume data, then were used to calculate the overlay thickness.On the other hand, Bina Marga Guideline calculated manually the overlay thickness based on the category of deflections. The results showed that Bina Marga Guidelines always produced less thickness than EVERSERIES program, i.e. 7.2 and 7.12 cm for direction A and B, respectively, compared with thicknesses produced by EVERSERIES, that is, 11.9 and 10.29 cm for direction A and B, respectively. This is because there is a difference in overview of pavement-layer distress between the two methods.